2018
DOI: 10.15252/embj.201798726
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming by histone acetyltransferase HAG1/AtGCN5 is required for pluripotency acquisition in Arabidopsis

Abstract: Shoot regeneration can be achieved through a two-step process involving the acquisition of pluripotency on callus-induction media (CIM) and the formation of shoots on shoot-induction media. Although the induction of root-meristem genes in callus has been noted recently, the mechanisms underlying their induction and their roles in shoot regeneration remain unanswered. Here, we show that the histone acetyltransferase HAG1/AtGCN5 is essential for shoot regeneration. In developing callus, it catalyzes histone acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 62 publications
4
101
0
Order By: Relevance
“…Interestingly, histone acetylation promotes wound-induced callus formation ( Fig. 6) but inhibits hormone-induced callus formation under in vitro conditions 50 . Thus, it appears that histone acetylation is not generally associated with onset of cell proliferation and callus formation, and that it is instead required for specific upstream processes during wound-induced callus formation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, histone acetylation promotes wound-induced callus formation ( Fig. 6) but inhibits hormone-induced callus formation under in vitro conditions 50 . Thus, it appears that histone acetylation is not generally associated with onset of cell proliferation and callus formation, and that it is instead required for specific upstream processes during wound-induced callus formation.…”
Section: Discussionmentioning
confidence: 96%
“…6). A recent study, showed that HAG1/GCN5-dependent histone acetylation is necessary for in vitro shoot regeneration 50 , by acetylating histones of several key root meristem genes, thereby activating their expression in hormone-induced callus. Our study thus together demonstrates a role for GNAT-MYST-mediated histone acetylation in both wound-and hormone-induced regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis GCN5 is implicated in regulating PLETHORA (PLT) gradient-mediated root stem cell niche maintenance and transit amplifying cell proliferation [21]. AtHAG1/GCN5 is involved in establishment of competence for de novo shoot regeneration through acting as an epigenetic switch that renders somatic cells to acquire regeneration potential via catalyzing histone acetylation at key root-meristem gene loci in developing callus [22].…”
Section: Introductionmentioning
confidence: 99%
“…This study by Kim et al (2018) not only offers significant novel insight into the mechanism of in vitro regeneration, but also provides entry points for important future studies. What are the first steps after treating explants with a high auxin/cytokinin hormone regime that eventually result in WOX and SCR gene upregulation?…”
mentioning
confidence: 95%